STRATEGY TO INCREASE THE COMPETITIVENESS OF THE E-COMMERCE SYSTEM ON TOKOPEDIA USING SWOT ANALYSIS - Bagas Pratama (Jurnal Scientia, 2023)
The development of information technology has entered a new phase which has affected various aspects of the life of the world community, including buying and selling. E-commerce has become the new prima donna in shopping for people around the world, including in Indonesia. The purpose of this research is to find out the weaknesses, strengths, opportunities and threats of Tokopedia. As well as knowing how Tokopedia implements its marketing strategy. The type of research used in this research is qualitative research. The results obtained are that Tokopedia is the safest business and has many conveniences in terms of service and service features and the various features have various benefits and can be easily accessed and access is certain and there are competitors in every business, there must be competitors. whatever, so is the online business.